Mahasiswa dan Peradaban Pemikiran (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2017)
Students are an inseparable part for the advancement and development of a civilization of the thinking of a nation. Students must become virus transmitters in social change so that students do not have a distance with the community. This is where students are required to have a great commitment to engage in a change and not as pretentious with various theories of change. What is needed by the intellectuals of students today is to make the knowledge and knowledge to reconstruct and redecorate various ideas of ideas that are not only enjoyed individually but can be held morally accountable so as to affect the pattern of fikir and positive behavior patterns for the community. Transformative thinking is the ultimate goal in which the realization of the civilization of thought is to put science on the goal of its basic principle in which science no longer seeks "for what it is" or "for what it is" but how science is able to translate how science should have a real impact to solve problems that exist in the life of nation and state.